Responding to the US national pollinator plan: a case study in Michigan. Issue 2 (15th November 2021) - Bloom, Elias H; Graham, Kelsey K; Haan, Nathan L; Heck, Ana R; Gut, Larry J; Landis, Douglas A; Milbrath, Meghan O; Quinlan, Gabriela M; Wilson, Julianna K; Zhang, Yajun; Szendrei, Zsofia; Isaacs, Rufus
Abstract : The long‐term health of pollinators is a critical issue for the functioning of natural habitats and for agricultural production. In response to widespread public concern about the future of these ecologically and economically important animals, in 2015 the US Government released a national strategy to support pollinators, including research priorities, directives for funding, and timelines for achieving three overarching goals. Five years after this strategic plan was released, we evaluate progress toward the national targets for improved honey bee ( Apis mellifera ) overwintering survival, expanded pollinator habitat, and larger monarch butterfly ( Danaus plexippus ) populations, and find that the three goals of the plan have not yet been reached. Our research and extension programs to improve the health of honey bees, wild bees, and monarch butterflies in the US state of Michigan are described, providing opportunities to contribute to the national pollinator goals.